SYNTHESIS and CHARACTERIZATION OF LIGAND TYPE ISOUREAS - Anaya M., Fernando (2001)
The N-Benzoyl-0-methyl - N1-(o-nitrophenyl)·isourea (L1) and N-Benzoyl-0-methyl·N1-(p-bromphenyl)-isourea (L2) ligands were slntheslzed by reactlon of the correspondlng N-Benzoyl-N1-phenyl-thioureas wlth mercury(II) acetate in methanolic solution. The characterlzation was made by elemental analysis, hydrogen (1H) and carbon (13C) Nuclear Magnetic Resonance, mass spectroscopy and the measure of their physical properties. The crlitallyne molecular structure of (L1) was determined by X-ray dlfraction.